Bochdalek hernia in an adult patient – Case report - Meta Jevtović, Ivana; Đokić, Bojan; Suša, Romana; Ćupurdija, Vojislav (Medicinski časopis, 2021)
INTRODUCTION: Bochdalek's hernia is a congenital defect localized on the posterolateral wall of the diaphragm through which the organs of the abdominal cavity pass into the chest. Primarily it is diagnosed in neonatal and postnatalatal periods, while in adults it is very rare.OVERVIEW: The authors present the case of Bochdalek's hernia in adulthood with symptoms arising from the gastrointestinal and respiratory tract. The diagnosis was confirmed by computerized tomography of the chest.CONCLUSION: Bochdalek's hernia is very rare in adulthood. Due to unspecific complaints from the gastrointestinal tract, it often remains unrecognizable. Radiological methods are of utmost importance in diagnostics, especially chest CT scan. Given the potential for potentially deadly complications, the surgical procedure is the choice of treatment for these patients.
Keywords: Bochdalek hernia; adults; computerized tomography